Identification of R2R3- MYB Transcription Factor (AtMYB13) as a Novel Substrate of Arabidopsis MPK3 and MPK6 - Hanh, Hoang Thi Minh; Nha, Nguyen Duong; Sik, Chung Woo (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Mitogen-activated protein kinase (MPK) cascades are signal transduction pathways that are highly conserved and widespread in all eukaryotic cells, including yeasts, animals and plants. MPKs play a central role for converting extracellular signals, including environmental stresses, into internal signal transduction and activation of intracellular responses. It is also well documented that plant MPKs are activated by a variety of environmental stimuli including salt, cold, wounding, heat, osmotic shock, heavy metal, UV, drought and pathogen attack. However, so far only a limited number of target molecules have been identified. Here, we report a MYB transcription factor, MYB13 that was identified as a novel substrate of MPKs in Arabidopsis. Using pull-down assays, MYB13 was shown to physically interact with MPK6 in vitro . MYB13 was phosphorylated by recombinant MPK3 and MPK6 proteins. By site-directed mutagenesis, Thr 71 and Ser138 of MYB13 were identified as the site of MPKs phosphorylation. These results indicated that the MPKs directly phosphorylate MYB13 in Arabidopsis . Keywords : MYB transcription factor, MAPK, phosphorylation